Poliuretanos biodegradáveis e nanocompósitos de argilominerais com efeito memória de forma - Iaci Miranda Pereira (2009)
In recent years, there has been increased interest in biodegradable polyurethane (PU) for use in biomedical; particularly the class of PUs with shape memory. In this thesis, six series of segmented PU with different hard segment content were prepared by the prepolymer mixing method in an aqueous environment. To improved PU properties further polyurethane/montmorillonite nanocomposites with different clay content were produced. PUs and their nanocomposites had their chemical structure, morphology, mechanical properties and shape memory properties investigated. The hydrolytic and alkaline degradation were also studied. The cellular viability and proliferation of cementoblasts and human mesenchymal stem cells were also investigated. Thetechniques applied were able to show that the hard-segment content and the hardsegment interactions were the two controlling factors for determining the structure of segmented PUs. Results showed that the degree of clay delamination within the polymer was able to tailor the phase morphology of the polymer. The polymer and the nanocomposites presented shape memory properties. The morphological changes during shape-memory cycles were examined. Recovery process was separated into three stages. The deformation cycle led to the formation of an oriented nanostructure derived from chain alignment. Bulk incompatibility and entropic recovery were the two controlling features for determining the final PU morphology. The recovery was observed to be alsotriggered by the strong interactions among hard domains. A relationship between the ability of the studied PU to recover their original shape and their original nanostructure was determined. Because the filler incorporation disturbs the formation of hydrogen bonds between amine and carbonyl group, interfering with the mobility of polymericchains and the metastable structure formed during deformation, shape recovery was reduced by the presence of nanoparticles. Obtained PUs were designed: (i) to work as guided tissue regeneration membranes to treat periodontal diseases and (ii) for the repair of articular cartilage defects through tissue engineering. Furthermore, we propose theuse of shape-memory polymer as anchoring system for a bladder sensor.